A ONE-PAGE METHOD FOR REINVENTING VALUE PROPOSITION IN CREATIVE INDUSTRY: A CASE STUDY OF INTUNE PRODUCTIONS - Eric Harianto; Monica Natalia; Yuanita Ratna Indudewi; Denpharanto Agung Krisprimandoyo (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
The ought to utilize music in promotions is developing each year, particularly when Covid-19 quickens the require for brands to go computerized. InTune Productions is a music production company based in Surabaya, Indonesia, that specializes in jingle, sound-logo and background music. The purpose of this research is to identify, distinguish, and decide the fitting client needs and fragment for InTune Productions, as well as to determine which innovative products and services are best suited to offer. The tool that is being used in this research is Value Proposition Canvas. Using qualitative descriptive method, this research is conducted from February 2021 to March 2022 with InTune Productions co-founders and customers as the primary data. The results of this study shows that Value Proposition Canvas has been helpful for InTune Productions to map its customer profiles. Value Proposition Canvas is demonstrated to be a reasonable apparatus to analyze customers’ pains and gains, as well as determining innovative products and services that are able to accommodate them.